Phyllanthus sanatanadharmae (Phyllanthaceae): a new species from southern Western Ghats, India - Mathew, Jose; Yohannan, Regy (Phytotaxa, 2021)
A new species of Phyllanthus (Phyllanthaceae: Eriococcus), P. sanatanadharmae, from the southern part of Western Ghats, India is described. Detailed taxonomic description and colour photographs are provided along with key to the section Eriococcus in Kerala region of Western Ghats.